Implementasi SCRUM Pada Pengenalan Aksara Lampung Menggunakan Augmented Reality - Arfiani, Ika; Nugraheni, Murien; Sulistyono, Danang (Forum Kerjasama Pendidikan Tinggi, 2021)
Lampung Province has 20 Lampung characters and 12 Lampung scripts as characters that need to be preserved. Lampung script learning is currently still using conventional methods so that many students begin to ignore this subject because it feels less interesting and boring. This study aims to build an application that can help users introduce Lampung script in the world of education on smartphones by applying Augmented Reality technology. By applying Marker Based Tracking which is one of the methods used in the development of Augmented Reality technology. This method works by recognizing and identifying patterns on markers to bring up virtual objects into the real environment. The system development uses the waterfall method with the stages of problem identification, initial planning, design and design, implementation, testing, and evaluation. This results in an Augmented Reality application to introduce Lampung script which is equipped with features showing 3D Lampung script, pronunciation of each Lampung script object, script gallery, guide for each menu and 20 Lampung script markers. Which type of smartphone camera can affect the application's ability to see objects at a certain angle to the marker, but is still quite safe at angles between 500 to 1800.